The Influence of Service Quality, Price and Brand Image on Honda Motorcycle Purchase Decisions in Solo Raya - Anindita Amelia; La Yandi; Andjar Hernanto (PT. Hidayat Muda Intelektual, 2026)
The ever-increasing competition in the Indonesian automotive sector requires motor vehicle manufacturers and distributors to understand the key determinants that shape consumer purchasing behavior. This study explores how service aspects, pricing strategies, and brand reputation influence consumer choices in purchasing Honda two-wheeled vehicles in the Solo Raya area. The research method applied is quantitative by collecting information directly from respondents through a structured digital survey aimed at Honda motorcycle users. Sampling was determined using a purposive technique with specific criteria, resulting in 78 research participants. The research construct includes three predictors (service quality, price, and brand image) and one outcome variable (purchase decision). Data processing applied multiple regression techniques using the SPSS 25th edition application, including validity tests, reliability tests, classical assumption tests, partial tests (t-tests), and coefficients of determination. Empirical findings reveal that the service dimension does not show a substantial impact on purchasing choices. In contrast, price and brand image factors show a substantial positive contribution, with brand image dominating as the strongest predictor. These results indicate that buyers prioritize price competitiveness and the strength of Honda's brand image over the service quality dimension in decision formulation. This research is expected to provide practical insights for distribution stakeholders and expand the academic literature on consumer dynamics in the national automotive sector.